60-GHz Half-Mode Substrate-Integrated Waveguide Bandpass Filter in 0.15-μm GaAs Technology - Liu, Xu-Juan; Wu, Wen; Xu, Kai-Da; Guo, Ying-Jiang; Chen, Qiang (Frontiers in Physics, 2021)
A compact 60-GHz on-chip bandpass filter (BPF) is presented using gallium arsenide (GaAs) technology. The miniaturization is achieved by half mode substrate integrated waveguide (HMSIW) structure. Finally, a prototype of the BPF is fabricated and tested to validate the proposed idea, whose simulated and measured results are in good agreement. The measurements show that it has a center frequency at 58.6 GHz with a bandwidth of 17.9%, and the minimum insertion loss within the passband is 1.2 dB. The chip, excluding the feedings, is only about 0.38λg×0.58λg, where λg is the guided wavelength at the center frequency.